Analysis of Industrial Waste Quality Control Using Generalized Variance and Hotelling’s T2 Control Diagram Methods - Hamidah, Isna; Hamid, Abdulloh; Khaulasari, Hani (Universitas Islam Indonesia, 2025)
Environmental pollution is an unsettling problem for everyone and the ecosystem which can be caused by poorly managed waste originated from the final output of industrial production processed. It can negatively impact the surrounding environment if it is not handled properly. Therefore, the waste must be processed until it meets the predetermined characteristic standards before being disposed of. Among the actions that can be taken is carrying quality control. This study aims to evaluate and characterize the quality of the waste produced. The methods used were the generalized variances and Hotelling’s T2 control charts. The data used for this research was the characteristics of liquid waste from a sugar factory industry, taken from May to September 2023. The quality control results, which were obtained using the generalized Variance control chart, could be statistically controlled after eight improvements. Then, Hotelling’s T2 control chart was successfully controlled after one test. The capability index value obtained was > 1, indicating that the quality control process in liquid waste at the Pesantren Baru sugar factory is capable or controlled.